2021
DOI: 10.1017/s1368980021002962
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to participant adherence of dietary recommendations within comprehensive cardiac rehabilitation programmes: a systematic review

Abstract: Objective: To identify individual-, provider- and system/environmental-level barriers and facilitators affecting cardiac rehabilitation (CR) participants’ adherence to dietary recommendations. Design: A systematic review of the medical literature was conducted. Six databases were searched from inception through March 2021: APA PsycInfo, CINAHL, Embase, Emcare, Medline and PubMed. Only those studies referring to barriers and facilitators reported by CR participants were considered. Pilot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…These findings are consistent across different scoping and narrative literature reviews. 34,35 The authors of a qualitative literature review identified that the cultural and religious beliefs of South Asian minorities living in the United Kingdom highly influence their involvement in physical activity and participation in other health practices. 34,35 To mitigate this challenge, religious leaders might be able to play a crucial role.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings are consistent across different scoping and narrative literature reviews. 34,35 The authors of a qualitative literature review identified that the cultural and religious beliefs of South Asian minorities living in the United Kingdom highly influence their involvement in physical activity and participation in other health practices. 34,35 To mitigate this challenge, religious leaders might be able to play a crucial role.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 The authors of a qualitative literature review identified that the cultural and religious beliefs of South Asian minorities living in the United Kingdom highly influence their involvement in physical activity and participation in other health practices. 34,35 To mitigate this challenge, religious leaders might be able to play a crucial role. There is some precedent in other ethnic groups that faith leaders can influence health behaviors not only at individual levels but also at community levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, while RE may be incorporated into some CR programmes, there is a clear emphasis on aerobic exercise-based CR (22)(23)(24)(25). Similarly, while Mediterranean diets are recommended to reduce CVD risk (26)(27)(28)(29)(30)(31)(32), there is little evidence for adherence to such dietary advice in current CR practices, particularly in non-Mediterranean populations (33,34). A randomized controlled trial (RCT) trialing a high-protein, Mediterranean-style diet combined with RE in a CR population would contribute evidence for the efficacy of such an approach.…”
Section: Introductionmentioning
confidence: 99%